Characterization and Genetic Diversity of Golden berries (Physalis spp.) Based on Morphological Characters - Sari, Hevia Purnama; Lestari, Mustika Adzania; Putrantri, Desty Aulia; Zulfahmi, Reza (Akta Agrosia, 2023)
Golden berries is a plant that has medicinal functions, fresh fruit and has high economic value. Golden berries  plant breeding is carried out to improve the quality of the plant. This research aims to analyze the genetic diversity of Golden berries  to produce new varieties. This research was conducted at the Lampung State Polytechnic Greenhouse from April to September 2023. This research used qualitative methods and the variables observed included variables in the vegetative and generative phases. The results showed that the five genotypes studied showed quite high diversity, namely at a copenhetic distance of 0.8. The golden 1 and golden 2 and red genotypes belong to Physalis peruviana while the two local genotypes are Physalis angulata. High diversity has great potential for crossbreeding so that it can produce heterosis traits. Heterosis is the characteristic of offspring being able to exceed the characteristics of their two parents. Based on this research, the genotypes observed are good for use as parents in plant breeding.